Pain, xerostomia, and younger age are major determinants of fatigue in Korean patients with primary Sjögren's syndrome: a cohort study. (2nd January 2017) - Koh, JH; Kwok, SK; Lee, J; Son, CN; Kim, J-M; Kim, HO; Park, SH; Sung, YK; Choe, JY; Lee, SS; Park, SH
Abstract : Objectives : Fatigue is a common clinical manifestation in patients with primary Sjögren's syndrome (pSS). The aims of this study were to investigate the association between fatigue severity and other clinical characteristics in pSS patients and to determine the factors contributing to fatigue. Method : We analysed 257 participants from the Korean Initiative of pSS (KISS), a prospective pSS cohort. Fatigue was assessed according to the fatigue domain of the European League Against Rheumatism (EULAR) Sjögren's Syndrome Patient-Reported Index (ESSPRI). Health-related quality of life (HRQoL) was evaluated using the EuroQol-5 dimensions (EQ-5D) questionnaire. Multiple linear regression analysis was used to estimate the effect of each variable on fatigue severity. Results : The median total ESSPRI score was 5 [interquartile range (IQR) 4–6]. Thirty-four per cent of patients reported a fatigue score > 5. Younger and premenopausal patients presented with more fatigue (p = 0.013 and p < 0.001, respectively). Higher Xerostomia Inventory (XI) scale (p < 0.001) and Ocular Surface Dryness Index (OSDI) (p < 0.001) scores were observed in patients with a fatigue score > 5. Pain, xerostomia, and age were determined to be significantly associated with fatigue severity after adjusting for depression/anxiety, OSDI score, and the presence of fibromyalgia using a multivariate general linear model. The ESSPRI fatigue score was correlated with the EQ-5D by time trade-off (TTO) values and visual analogue scale (VAS) scores. Conclusions : In Korean patients with pSS, younger age, xerostomia, and pain were correlated significantly with fatigue, and fatigue was associated with HRQoL.